Beyond Pity: Dialectics of Religious Authority, Social Capital, and Stigma in Intellectual Disability Marriage - Sallom, Dea Salma; Hilmy, Masdar; Apipudin , Syamsudin (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2025)
Marriage involving persons with intellectual disabilities remains a contested issue within Islamic family law, particularly at the intersection of religious norms, social values, and stigma. While the right to marry is normatively recognized, its practical implementation often reveals tensions between protection, autonomy, and societal expectations. This study aims to examine how the dialectics of religious authority, social capital, and stigma shape the practice of marriage between persons with intellectual disabilities and non-disabled partners in Muslim communities. Employing a socio-legal approach, this research is based on in-depth interviews, participant observation, and documentation conducted in Gresik, Indonesia. The data were analyzed thematically using Pierre Bourdieu’s framework of habitus, capital, and field. The findings reveal three major points. First, religious-cultural habitus constructs marriage as a moral obligation, often driving families to arrange marriages as a form of protection and preservation of social honor. Second, religious and social capital function as key survival strategies, providing both moral legitimacy and practical support for sustaining the household. Third, persistent social stigma operates as symbolic violence that questions the couple’s kafa’ah (marital compatibility) and limits their social inclusion. This study argues that marriage involving persons with intellectual disabilities is not merely an individual decision but a product of complex social negotiations shaped by competing structures of legitimacy and exclusion. Therefore, it highlights the urgency of reinterpreting Islamic family law in a more inclusive manner and strengthening institutional support to ensure the dignity, autonomy, and equal rights of persons with disabilities in marital life.